Prevention of severe pitting corrosion of 13Cr pipeline steel by a sulfate reducing bacterium using a green biocide cocktail - Xu, Lingjun; Khan, Adnan; Kijkla, Pruch; Kumseranee, Sith; Punpruk, Suchada; Gu, Tingyue (Frontiers in Materials, 2024)
To combat abiotic CO2 corrosion of pipelines, chromium steels (CrSs) are used to replace carbon steels, but CrSs can suffer very severe pitting corrosion caused by microbiologically influenced corrosion (MIC) because their passive films are not as good as those on high-grade stainless steels, and their MIC often involves (semi-)conductive corrosion product films. In this study, severe pitting corrosion (2.0 cm/a pitting corrosion rate) with a 7-day weight loss of 3.8 ± 0.5 mg/cm 2 (0.26 mm/a uniform corrosion rate) was observed on 13Cr coupons incubated anaerobically with a highly corrosive pure-strain sulfate reducing bacterium (SRB) Desulfovibrio ferrophilus IS5 in 125 mL anaerobic vials filled with 50 mL enriched artificial seawater at 28 o C. A popular green biocide, namely tetrakis hydroxymethyl phosphonium sulfate (THPS), was enhanced by biofilm dispersing Peptide A (a 14mer) to mitigate SRB MIC against 13Cr. The 7-day weight losses for coupons with 50 ppm (w/w) THPS, 50 ppm THPS + 100 nM (180 ppb) Peptide A and 100 ppm THPS were reduced to 2.2 ± 0.2 mg/cm 2 , 1.5 ± 0.5 mg/cm 2 and 0.3 ± 0.2 mg/cm 2 , respectively. The pitting rates also decreased from 20 mm/a to 12 mm/a, 8.6 mm/a, and 1.5 mm/a, respectively based on the maximum pit depth data for the 7-day incubation. Electrochemical tests using a miniature electrochemical glass cell design supported the weight loss trend with additional transient corrosion rate information. THPS was found to be effective in mitigating severe pitting corrosion on 13Cr, and the enhancement effect of Peptide A for THPS was manifested. This work has significant implications in field applications when CrSs are considered as metal choices to replace carbon steels to combat abiotic CO2 corrosion in pipelines. When SRB MIC is a possible threat, a mitigation plan needs to be implemented to prevent potentially very severe pitting that can lead to pinhole leaks.